PENGARUH LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (The Effect Of Liquidity, Profitability, And Company Size On Financial Distress) - Susanti, Popi; Ismawati, Kun (STIE Atma Bhakti, 2024)
The present investigation aims to determine the influence of liquidity, profitability, and company size on financial distress in textile and garment sub sector companies listed on the IDX in 2021-2023. This reserch is a quantitative research. The sampling technique is the study uses purposive sampling by taking secondary data from the official website www.idx.co.id. The population of this study is 23 companies with 6 companies as a sample. The analysis techniques used are descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The findings of this investigation indicate that in part, cash position influences financial distress, profitability and company size do not have aneffect on financial distress. While simultaneously liquidity, profitability, and company size have an affect on financial distress.